Ecological footprint as an indicator of sustainability at Lisbon School of Health Technology, Portugal - Francisco, Sara (2014)
Higher education institutions, has an active role in the development of a sustainable future and for this reason, it is essential that they became environmentally sustainable institutions, applying methods such as the Ecological Footprint analysis. This study intent is to strengthen the potential of the ecological footprint as an indicator of the sustainability of students of Lisbon School of Health Technology, and identify the relationship between the ecological footprint and the different socio-demographic variables.